Pengaruh Manajemen Kepemimpinan Dan Kebijakan Jadwal Berpola Teknologi dan Informasi Terhadap Pembelajaran Di Jurusan Teknik Elektronika - Andhika Herayono; Elsa Sabrina; Firdaus Firdaus; Dedy Irfan; Hansi Effendi (UIN Sumatera Utara, 2021)
Management and leadership are two different things that are brought together to achieve the goals of a group of fields. Leadership management is a form of leadership skills as a form of skills to lead, direct and motivate effectively and efficiently. One of them is with a policy that is a method that can be used by almost every group. Electronic Engineering is one of the majors that participate in providing policies on learning schedules in teaching and learning activities. Schedule policies can affect productivity and learning outcomes. The study schedule is still adjusted to any existing conditions. A field survey has been conducted during the learning process carried out by the Department of Electronics Engineering. This is proven by conducting a survey of the condition of the students of the Department of Electronics Engineering when carrying out the learning process on campus during advance, and during the learning process using internet access (remotely).Keywords: